The Relationship of Community Identification to Brand Community Engagement and its Influence on Co-Creation of Community Functional Support and Community Commitment - Syaifuddin, Syaifuddin; Nasution, Aulia Arief; Matondang, Sofiyan (Jurnal Manajemen Dayasaing, 2024)
The development of a company requires various processes and cooperation in various sectors in the company. Including in the development of product marketing in marketing the brand community. Therefore, this study will test whether there is a Relationship between Community Identification and Brand Community Involvement and its influence on Co-Creation of Community Functional Support and Community Commitment. Data collection using explanatory methods and secondary data analysis. The results of the study indicate that Community Identification has a significant positive effect on Community Involvement. Likewise, Community Involvement has a significant positive effect on Co-Creation of Community Functional Support. Furthermore, Community Involvement also has a significant positive effect on Community Commitment. Likewise, Co-Creation of Community Functional Support has a significant positive effect on Community Commitment. So it is concluded that each variable has a relationship in the company.